Applied computer sciences in engineering : third Workshop on Engineering Applications, WEA 2016, Bogotá, Colombia, September 21-23, 2016, Revised selected papers /: third Workshop on Engineering Applications, WEA 2016, Bogotá, Colombia, September 21-23, 2016, Revised selected papers. (2016) - Unknown
No abstract available